2004
DOI: 10.1099/mic.0.26846-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cyst cell formation in the purple photosynthetic bacterium Rhodospirillum centenum

Abstract: Rhodospirillum centenum is an anoxygenic photosynthetic bacterium that is capable of differentiating into several cell types. When grown phototrophically in liquid, cells exhibit a vibrioid shape and have a single polar flagellum. When grown on a solid surface, R. centenum will differentiate into rod-shaped swarm cells that display numerous lateral flagella. Upon starvation for nutrients, R. centenum also forms desiccation-resistant cysts. In this study, it was determined that R. centenum has heat- and desicca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 33 publications
1
60
0
Order By: Relevance
“…The conservation of these motifs lends support to the theory first presented in Hallez et al (23) that CtrA mediates cell division through direct regulation of minC transcription in α-proteobacteria containing the Min system and through direct regulation of ftsZ in C. crescentus and other α-proteobacteria that lack the Min system. It is intriguing that a single regulatory factor can retain its role in a process so highly conserved as cell division but simultaneously demonstrates the flexibility to modulate diverse cellular differentiation events central to the lifestyles of α-proteobacteria, which can range from cyst cell formation in Rhodospirillum centenum to intracellular pathogenesis in Brucella (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…The conservation of these motifs lends support to the theory first presented in Hallez et al (23) that CtrA mediates cell division through direct regulation of minC transcription in α-proteobacteria containing the Min system and through direct regulation of ftsZ in C. crescentus and other α-proteobacteria that lack the Min system. It is intriguing that a single regulatory factor can retain its role in a process so highly conserved as cell division but simultaneously demonstrates the flexibility to modulate diverse cellular differentiation events central to the lifestyles of α-proteobacteria, which can range from cyst cell formation in Rhodospirillum centenum to intracellular pathogenesis in Brucella (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Many bacterial species undergo cell development to a dormant cell or spore under low nutrient stress (Berleman & Bauer, 2004;Bacun-Druzina et al, 2007;Lindsay et al, 2006), but most bacteria lack the morphological complexity of Myx. xanthus or the myxobacteria in general.…”
Section: Predatory Life Cyclementioning
confidence: 99%
“…Although fruiting-body formation is often referred to as a developmental programme, models of population-wide, uniform decision making (Kroos, 1990;Giglio et al, 2011) seem insufficient at explaining the role of multicellular structures observed during predatory behaviour. Indeed, many bacterial species will convert a fraction of the population to dormant cells or spores under low nutrient stress (Berleman & Bauer, 2004;Bacun-Druzina et al, 2007;Lindsay et al, 2006), yet Myx. xanthus fruiting bodies have an unmatched level of cell-type segregation.…”
Section: Cellular Development and Multicellular Behaviourmentioning
confidence: 99%
“…in that the entire cell converts to a myxospore, which is also the case during Rhodospirillum sp. bacterial cyst formation (6). During these developmental transitions, gene expression and the pattern of cell movements are highly regulated (112).…”
Section: Introductionmentioning
confidence: 99%